Pengaruh Efikasi Diri dan Ekspektasi Hasil terhadap Niat Mahasiswa Berkarir di Bidang Akuntansi Pemerintahan: Studi Empiris pada Mahasiswa Jurusan Akuntansi di Kota Padang - Umbratul Nada; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2023)
This research examines the effect of self-efficacy and outcome expectations on students' intentions to have a career in government accounting (an empirical study of accounting majors in Padang City). The population of this study was S1 students majoring in accounting in Padang City. The sample in this research was 365 samples. Type this research is a causal research with a quantitative approach.The source of data in this research is primary data. Data collection techniques with questionnaires distributed to students. Data analysis using multiple linear regression analysis. The results showed that self-efficacy and outcome expectations have a positive effect on student intentions career in government accounting.